The impact of transitions between two‐fluid and three‐fluid phases on fluid configuration and fluid‐fluid interfacial area in porous media. Issue 9 (5th September 2015) - Carroll, Kenneth C.; McDonald, Kieran; Marble, Justin; Russo, Ann E.; Brusseau, Mark L.
Abstract Multiphase‐fluid distribution and flow is inherent in numerous areas of hydrology. Yet pore‐scale characterization of transitions between two and three immiscible fluids is limited. The objective of this study was to examine the impact of such transitions on the pore‐scale configuration of organic liquid in a multifluid system comprising natural porous media. Three‐dimensional images of an organic liquid (trichloroethene) in two‐phase (organic‐liquid/water) and three‐phase (air/organic‐liquid/water) systems were obtained using X‐ray microtomography before and after drainage and imbibition. Upon transition from a two‐phase to a three‐phase system, a significant portion of the organic liquid (intermediate wetting fluid) was observed to exist as lenses and films in contact with air (nonwetting fluid). In these cases, the air was either encased by or contiguous to the organic liquid. The presence of air resulted in an increase in the surface‐area‐to‐volume ratios for the organic‐liquid blobs. Upon imbibition, the air was displaced downgradient, and concomitantly, the morphology of the organic‐liquid blobs no longer in contact with air reverted to that characteristic of a two‐phase distribution (i.e., more spherical blobs and ganglia). This change in morphology resulted in a reduction in the surface‐area‐to‐volume ratio. These results illustrate the impact of transitions between two‐phase and three‐phase conditions on fluid configuration, and they demonstrate the malleable nature of fluid configuration under dynamic, multiphase‐flow conditions. The results have implications for characterizing and modeling pore‐scale flow and mass transfer processes.